2018
DOI: 10.1200/jco.2017.76.2187
|View full text |Cite|
|
Sign up to set email alerts
|

FOLFOX or CAPOX in Stage II to III Colon Cancer: Efficacy Results of the Italian Three or Six Colon Adjuvant Trial

Abstract: Purpose Given the cumulative neurotoxicity associated with oxaliplatin, a shorter duration of adjuvant therapy, if equally efficacious, would be advantageous for patients and health-care systems. Methods The Three or Six Colon Adjuvant trial is an open-label, phase III, multicenter, noninferiority trial randomizing patients with high-risk stage II or stage III colon cancer to receive 3 months or 6 months of FOLFOX (fluorouracil, leucovorin, and oxaliplatin) or CAPOX (capecitabine plus oxaliplatin). Primary end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 12 publications
(9 reference statements)
5
64
0
1
Order By: Relevance
“…The TOSCA trial is an open‐label, phase III, multicenter noninferiority trial that randomized patients with high‐risk stage II or stage III CC to receive 3 or 6 months of FOLFOX‐4/CAPOX adjuvant chemotherapy (ChT). The trial failed to demonstrate a formal noninferiority of 3 months versus 6 months of treatment .…”
Section: Introductionmentioning
confidence: 98%
“…The TOSCA trial is an open‐label, phase III, multicenter noninferiority trial that randomized patients with high‐risk stage II or stage III CC to receive 3 or 6 months of FOLFOX‐4/CAPOX adjuvant chemotherapy (ChT). The trial failed to demonstrate a formal noninferiority of 3 months versus 6 months of treatment .…”
Section: Introductionmentioning
confidence: 98%
“…The primary end point was relapse-free survival (RFS), defined as the time from the date of randomization up to the date of the first relapse or death from any cause. At the primary analysis, 5 the trial failed to formally show non-inferiority of 3 versus 6 months of treatment to the predefined margin of 20% relative increase. However, in the low risk population (pN1 disease), the 3 months was similar to the 6-months duration in term of RFS.…”
Section: Tosca Trial Overviewmentioning
confidence: 99%
“…Our ndings from population-based cancer registry data con rmed that higher chemotherapy RDI was needed in high-risk stage III colon cancers, compared with low-risk cancers, and are consistent with the conclusions from six randomized, phase 3 clinical trials conducted by the International Duration Evaluation of Adjuvant Therapy (IDEA) collaboration, which found that 6 months of FOLFOX particularly bene ted high-risk stage III colon cancers. These clinical trials evaluated whether 3 months of FOLFOX or CAPOX is non-inferior to 6 months of therapy in the rate of disease-free survival at 3 years [4,9,32,33]. Results from a pooled analysis of six trials showed that in stage III colon cancer patients treated with FOLFOX, 6-month therapy had a higher rate of disease-free survival than 3-month therapy, particularly in the high-risk group [9].…”
Section: Discussionmentioning
confidence: 99%
“…FOLFOX (Oxaliplatin, uorouracil aka 5-FU, and leucovorin) is one of the standard adjuvant therapies commonly administered [2][3][4].…”
Section: Introductionmentioning
confidence: 99%